Heart Failure Induced by Perinatal Ablation of Cardiac Myosin Light Chain Kinase - Islam, Yasmin F. K.; Joseph, Ryan; Chowdhury, Rajib R.; Anderson, Robert H.; Kasahara, Hideko (Frontiers in Physiology, 2016)
Background: Germline knockout mice are invaluable in understanding the function of the targeted genes. Sometimes, however, unexpected phenotypes are encountered, due in part to the activation of compensatory mechanisms. Germline ablation of cardiac myosin light chain kinase (cMLCK) causes mild cardiac dysfunction with cardiomyocyte hypertrophy, whereas ablation in adult hearts results in acute heart failure with cardiomyocyte atrophy. We hypothesized that compensation after ablation of cMLCK is dependent on developmental staging and perinatal-onset of cMLCK ablation will result in more evident heart failure than germline ablation, but less profound when compared to adult-onset ablation. Methods and Results: The floxed-Mylk3 gene was ablated at the beginning of the perinatal stage using a single intra-peritoneal tamoxifen injection of 50 mg/kg into pregnant mice on the 19th day of gestation, this being the final day of gestation. The level of cMLCK protein level could no longer be detected 3 days after the injection, with these mice hereafter denoted as the perinatal Mylk3-KO. At postnatal day 19, shortly before weaning age, these mice showed reduced cardiac contractility with a fractional shortening 22.8 ± 1.0% (n = 7) as opposed to 31.4 ± 1.0% (n = 11) in controls. The ratio of the heart weight relative to body weight was significantly increased at 6.68 ± 0.28 mg/g (n = 12) relative to the two control groups, 5.90 ± 0.16 (flox/flox, n = 11) and 5.81 ± 0.33 (wild/wild/Cre, n = 5), accompanied by reduced body weight. Furthermore, their cardiomyocytes were elongated without thickening, with a long-axis of 101.8 ± 2.4 μm (n = 320) as opposed to 87.1 ± 1.6 μm (n = 360) in the controls. Conclusion: Perinatal ablation of cMLCK produces an increase of heart weight/body weight ratio, a reduction of contractility, and an increase in the expression of fetal genes. The perinatal Mylk3-KO cardiomyocytes were elongated in the absence of thickening, differing from the compensatory hypertrophy shown in the germline knockout, and the cardomyocyte thinning shown in adult-inducible knockout.